"Hot" and "Cool": Perceptions of Subtropical Modernism in Post-war Queensland. Issue 2 (4th May 2017) - Musgrave, Elizabeth
Abstract: In 1960s Queensland, scientifically validated principles for climate design provided a convenient evidential basis for justifying modern architecture. The two constructs, modernism and climate responsive design, became conflated in the haste to isolate a distinctive architectural identity for Queensland. A suppression of complexities has seen climate zone boundaries collapse into state boundaries and the architecture of tropical and subtropical zones illustrated with work predominantly located in the populous southeast corner. Climate, whilst defined very loosely, is usually addressed empirically in explanations about design processes and outcomes with little consideration given to the variety of ways that climate might inform a culture of architecture. Together with the frequency and range of situations labelled "sub-tropical, " these issues challenge the usefulness of climate as a critical tool for assessing the development of Queensland architecture. This paper evaluates the significance of climate to the consolidation of modern architecture in Queensland and tests the veracity of claims for a subtropical modernism there. It uses the writing and built work of renowned Brisbane architect, artist, essayist, correspondent, John Dalton (1927–2007), as a reference point for revealing tensions in local approaches to climate responsiveness and regional design. Dalton was conscious of the possibilities for a distinctively Queensland culture of modern architecture and his built work demonstrates the development of a set of private theories and practices that defy the reduction favoured by discourse, between modernist and regionalist thinking.